Amazing Facts Space: Go facts! - Aureole Publishing; Aureole Publishing (Aureole Publishing: UK, 2004)
Introduces young readers to fascinating aspects of space, including planets. Through engaging facts and vivid illustrations, the book explains complex astronomical concepts in an accessible manner, fostering curiosity and learning about the universe.
The nine Planets -- Earth -- Mercury and Venus -- Mars -- Jupiter and Saturn -- Uranus, Neotune and Pluto.
Includes full-color illustrations and photographs.
Ages 7-10.
Text in English.
Hard binding.
Keywords: Space; Planets. -- Juvenile literature